Textiles - Malinauskiene, Laura; Morgardt-Ryberg, Kristina (Quick Guide to Contact Dermatitis, 2015)
Allergic contact dermatitis (ACD) caused by textile dyes is not uncommon. The main dye allergens belong to disperse dyes which are used for coloring synthetic textile fibers. The European baseline series is not suitable for the reliable detection of textile dye allergy although p-phenylenediamine has been considered as a marker for contact allergy to disperse azo dyes. In order to diagnose ACD from textile dyes, a high index of suspicion is required. Textile-related dermatitis most commonly develops on the extremities, followed by the trunk, face, genitalia, buttocks, and in the folds but may also have unusual clinical patterns. Consider possible contact allergy to textile dyes if dermatitis appears on symmetrical sites of intimate contact with the garment. Perform patch testing with the European baseline series and with additional textile dye series. Testing with the garment or with an extract of the suspected textile as well as a challenge test with the article of clothing (stop and wear again) can also be recommended.
Publisher Copyright: © Springer-Verlag Berlin Heidelberg 2016.